METHOD OF SYSTEMATIC INSPECTION FOR SOLVING DIFFERENTIAL EQUATIONS: Case Studies - Sammour, Yousif Tawfiq (IJRDO -JOURNAL OF MATHEMATICS, 2018)
The method of systematic inspection solves or helps in discovering the behavior of differential equations. This method solves differential equations by creating functions of the independent variable(s) from two opposite small functions called seeds. Starting with a seed you can build a bigger function. Adding the two opposite functions together will give a function that satisfies the differential equation. 2000 mathematics subject classification. 34A30, 35G15, 34A34,35E99